1D and 3D supramolecular structures exhibiting weak ferromagnetism in three Cu(II) complexes based on malonato and di-alkyl-2, 2'-bipyridines. Issue 9 (2nd May 2016) - Jaramillo-García, Jonathan; Téllez-López, Antonio; Martínez-Domínguez, Rogelio; Morales-Luckie, Raul A.; Martínez-Otero, Diego; Sánchez-Mendieta, Víctor; Escudero, Roberto
Abstract: Three new Cu(II) complexes composed of malonato (mal), methylmalonato (memal), 4, 4′-di-tert-butyl-2, 2′-bipyridine (tbpy) and 5, 5′-dimethyl-2, 2′-bipyridine (mebpy) ligands, Cu(H2 O)(mal)(tbpy) (1 ), Cu(H2 O)(memal)(tbpy) (2 ) and Cu4 (H2 O)4 (memal)4 (mebpy)4 ·11H2 O (3 ) were synthesized by simple one-pot solution reactions at ambient conditions. Single-crystal X-ray diffraction analyses reveal that the Cu(II) ions exhibit a distorted five-coordinate square pyramidal geometry. These three complexes display supramolecular arrays due to hydrogen-bonding interactions. Complexes1 and2 show 1-D supramolecular structures;1 forms a double-ion chain, unlike2, which only generates a single-ion chain. In3, there are two identical monomers in the asymmetric unit with Z″  = 2; its high number of noncoordinated water molecules, along with hydrogen-bonding interactions between aqua ligand and memal ligand, generate a supramolecular tetramer, which mimics to produce a 3-D supramolecular framework. Besides this fascinating and yet uncommon crystallographic phenomenon in3, the structural differences found in these complexes arise from the substituted groups in the malonato dianion and in the bipyridine ligands. These compounds exhibit weak ferromagnetic-exchange interactions. Abstract :